Penggunaan Media Pembelajaran Online Selama Covid-19 dalam Pendidikan Jasmani Olahraga dan Kesehatan Sekolah Menengah Pertama Negeri Se-Kecamatan Darangdan - Asmira Rihani; Fahrudin Fahrudin; Muhammad Mury Syafei (Jurnal Ilmiah Wahana Pendidikan, 2021)
Indonesia and even the world is being hit by the spread of the corona virus or Corona Virus Disease 2019 (Covid-19). With the Covid-19 pandemic, the teaching and learning process (KBM) at SMPNs throughout the Darangdan District uses an online learning system. This study aims to determine the use of online learning media during covid-19 in physical education, sports and health at state junior high schools in the district of Darangdan. This research is quantitative descriptive. The method used in this study is a survey method, the data collection technique used is by making an online questionnaire using google form. the level of use of online learning media during covid-19 in physical education, sports and health at State Junior High Schools in the District of Darang and Purwakarta Regency was in the "very high" category of 0.00% (0 teachers), "high" of 30.77 % (4 teachers), 38.46% (5 teachers), “low” 15.38% (2 teachers), and 15.38% very low (2 teachers). Based on the above average, which is 13.46, it is in the sufficient category